TECHNOLOGICAL FACTORS AND SOCIAL MEDIA ADOPTION AMONG MICRO-ENTERPRISES: THE MODERATING ROLE OF PERSONAL INNOVATIVENESS - Hernando, Hendrick; Shahzad, Sobia; Nurmalasari, Niza (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2025)
Introduction: Adopting social media has many benefits for micro-enterprises, particularly in terms of greater marketing exposure. Thus, identification of social media adoption and the associated determinants is essential. This study sets a moderating variable to fill the identified gap in previous studies. Besides, the influence of technological factors as social media adoption determinants is evaluated. Methods: Employing a purposive sampling procedure, data were obtained via questionnaires distributed to owners or managers of micro-enterprises in Madiun. A total of 120 valid responses were analyzed using partial least squares structural equation modeling (PLS-SEM). Results: The results of this study showed that cost-effectiveness and perceived compatibility positively affect the adoption of social media apps, while relative advantage has no significant influence. Our findings also found that personal innovativeness significantly moderates the relationship between relative advantage and social media adoption. Conclusion and suggestion: As a novel contribution, this study has confirmed the moderating role of personal innovativeness, while some advice for stakeholders, including government and platform developers, is provided.